Task engagement, learner motivation and avatar identities of struggling English language learners in the 3D virtual world. (February 2020) - ChengChiang Chen, Julian; Kent, Sarah
Abstract: This study investigated at-risk ESL learners' task performance and attitudes towards a 3D approach of improving their English spoken and written communication skills in Second Life (SL). It documented how these SL "newbies, " who had not previously experienced 3D virtual learning, carried out SL-enabled, real-life oriented and interactive tasks. Qualitative data were triangulated from students' weekly blog entries, reflective essay writing and a focus group interview, followed by a thematic analysis approach. Despite the technical glitches impeding the flow of virtual class management and causing communication breakdown, students overall held positive perceptions of the task-based design implemented in SL. Unique SL affordances were found to maximise task execution and engagement, thus fostering more authentic and crosscultural communication, building confidence, boosting motivation, and empowering learners via avatar anonymity. The game factor also transformed a conventional English class into a fun virtual learning playground. Such findings not only highlight pedagogical suggestions for curriculum design and language program improvement, but also implicate both challenges and possibilities of conducting research and teaching at-risk language learners in a 3D sphere. Highlights: SL affordances promote authentic and crosscultural communication. Task-based design in SL enhances learners' engagement and investment in tasks. Avatar anonymity empowers at-risk ESL learners. SL-enabled tasks infuse the game factor in language learning and boost motivation.